Feed-lot of lambs from different biotype and live weight: effect on carcass characteristics and meat quality - Bianchi, G.; Garibotto, G.; Bentancur, O.; Forichi, S.; Ballesteros, F.; Nan, F.; Franco, J.; Feed, O. (Agrociencia Uruguay, 2006)
In the Experimental Station “Dr. Mario A. Cassinoni” (EEMAC) of the Agronomy Faculty (Paysandú, Uruguay; 32.5º south latitude y 58º west longitude), the initial feedlot weight (24.9± 3.4 y 34.1 ± 3.1 kg) and the genetic type (Poll Dorset x Corriedale, Dohne Merino X Corriedale, Southdown x Corriedale y Highlander x Corriedale) on carcass and meat characteristics of heavy lambs reared on pastures and feed – lot finished was studied. A complete randomized experimental design with factorial arrangement of treatments and 3 repetitions, was used. The use of meat breeds in terminal crossbreeding and feedlot beginning live weight originated differences in carcass characteristics, with out major changes in meat quality, which depend of muscle type was evaluated.